Gumshoes and blanket wings: care in pandemic performances for youth - Fitzsimmons Frey, Heather (My University, 2021)
When Canadian theatrical performances halted because of the pandemic, artists everywhere bravely reimagined their work. Creating for any remote audience is difficult, but young audiences present particular challenges. Danish artists Peter Manscher and Peter Jankovic (qtd. in Reason 46) explain that in successful child-focused work, spectators “must have the feeling that it would have been different if they hadn’t been there—that their presence matters.” How can children feel their presence matters if a performance streams regardless of a child’s presence? Foolish Operations’ Artistic Director Julie Lebel asserts “Working with children in general and the very young especially implies interactivity. To provide static content doesn’t do the job.” The issue of presence is also related to a second challenge of utmost importance for young audiences: relationship. What kinds of meaningful performance-fostered relationships are possible during this pandemic? In response to pandemic restrictions, Outside the March (Toronto) and Foolish Operations (Vancouver) reimagined projects for young audiences thoughtfully and very differently, but both companies decided that some of their pandemic pivots would avoid screens altogether, and their creative work would focus on intimacy, interactivity, and relationships. Outside the March’s Ministry of Mundane Mysteries Playdate Edition, and Foolish Operations’ Moving, Resting, Nesting boldly use limitations placed on artists and audiences to create opportunities in which a child’s presence matters. While Outside the March is interested in forging relationships between people who cannot be together because of the pandemic, Foolish Operations was interested in “supporting the family unit as the site of the experience.” Through content and dramaturgy that centralize relationships, intimacy, and audience care, each project considers what young people and their caregivers might be craving from a performance experience right now.
Keywords: pandemics; theatre; children; interactivity; relationships; performance